The role of municipal government in forming social security - Leszczyński, Marek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
The dynamics of economic, political and social changes constantly poses new threats to the existence and creative development of entities (public as well as human communities). The state remains the main entity that is responsible for creating the basics of security, yet it is crucial to study the ways and methods of forming social security for local communities. Under the approved political system, a significant role in ensuring security is ascribed to municipal governments and local governments’ institutions. Of key importance are efficiency and effectiveness in functioning of the local authorities as they greatly determine the citizens’ standard of living . Furthe rmore, an important area is the cooperation of local governments with entities responsible for social security (the entities belonging, among others, to the National Rescue and Fire Fighting System and the National Medical Emergency Services). This paper raises an issue of forming social security at a local level with the use of the logistical approach. An improvement in more effective provision of the social security is possible by using the logistical methods as well as social logistics philosophy. This philosophy aims to focus on achieving social goals and tends to attach less importance to the economics of its objectives. It is a relatively new approach that complements the traditional perception of military and business logistics. The constantly increasing numer of social threats makes one search for effective methods of reducing their effects and the help for people who are excluded or marginalised for various reasons. Moreover, the public administration, which plays important functions as serving administration, constantly needs to improve the ways of achieving goals connected to fulfilling its mission of a public character.

Dynamika zmian ekonomicznych, politycznych i społecznych powoduje, że ciągle pojawiają się nowe zagrożenia dla trwania i kreatywnego rozwoju podmiotów (państwowych oraz wspólnot ludzkich). Państwo pozostaje głównym podmiotem odpowiedzialnym za tworzenie podstaw bezpieczeństwa, przy czym istotne jest badanie sposobów i metod kształtowania bezpieczeństwa wspólnot lokalnych. W przyjętych rozwiązaniach ustrojowych istotną rolę w zapewnieniu bezpieczeństwa przypisano samorządowi terytorialnemu i instytucjom samorządowym. Kluczową kwestią jest sprawność i skuteczność funkcjonowania podmiotów samorządowych, bo od tego w znacznym stopniu zależy jakość życia obywateli. Ponadto ważnym obszarem pozostaje współpraca organów samorządu terytorialnego z podmiotami odpowiedzialnymi za bezpieczeństwo społeczne (podmioty przypisane m.in. do Krajowego Systemu Ratowniczo-Gaśniczego oraz Państwowego Ratownictwa Medycznego). W tekście poruszono kwestię kształtowania bezpieczeństwa społecznego na poziomie lokalnym z wykorzystaniem podejścia logistycznego. Poprawa skuteczności zapewnienia bezpieczeństwa społecznego jest możliwa przy wykorzystaniu metod logistycznych oraz filozofii logistyki społecznej ukierunkowanej na realizację celów społecznych, a w mniejszym stopniu kierującej się ekonomicznością celów. Jest to stosunkowo nowe podejście, stanowiące uzupełnienie tradycyjnie postrzeganej logistyki militarnej oraz logistyki biznesowej. Zwiększająca się nieustannie liczba zagrożeń o charakterze społecznym skłania do poszukiwania skutecznych metod niwelowania ich skutków oraz pomocy dla osób z różnych powodów wykluczonych, bądź zmarginalizowanych. Ponadto administracja publiczna, która wykonuje ważne funkcje z zakresu administracji świadczącej nieustannie musi doskonalić sposoby osiągania celów związanych z wypełnianiem swojej misji o charakterze publicznym.
Samorząd terytorialny w kształtowaniu bezpieczeństwa społecznego
Keywords: social security; security of local communities; bezpieczeństwo społeczne; bezpieczeństwo społeczności lokalnych